The acceptance factor of solar energy product among the consumers in Rembia, Malacca / Aishah Mohamad Zafir and Anis Thurayya Mohamad Rodzi - Mohamad Zafir, Aishah; Mohamad Rodzi, Anis Thurayya (Faculty of Business Management, 2016)
The research was conducted to carry out a study entitled “The Acceptance Factors Of Solar Energy Product in Rembia, Malacca”.This research was conducted to carry out a study entitled “The Acceptance Factors of Solar Energy Product in Rembia, Malacca. The purpose of this study is to understand the relationship between four variables which are the Knowledge, Effort Expectancy, Social Influence, and Performance Expectancy with the dependent variable which is the Acceptance Factor of Solar Energy Product. In this study, the research objective tht have been identified are, to determine the level of acceptance of solar energy product among the consumers, to verify the relationship between acceptance factor and acceptance of solar energy product among the consumers as well as to examine the relationship between the consumers and their adoption to the green technology product. For this study, 1,497 people are estimated residing in Rembia Malacca. The highest number of the sample size which is 150 is selected. At the end of the distribution, 123 respondents had returned their responses while the others are considered as unfinished. . The data was obtained from primary data by using questionnaires. All data collected through the questionnaires were analyzed systematically by Statistical Package for Social Science (SPSS) version 20.0. Energy came in a various form such as water energy, coal, oil and gas and etc. Things can be fulfilled or function by using the energy. In simple words, energy is a part of our daily life routine. For example, energy is required for the basic human needs such as cooking, heating water, lighting and other household activities. Energy is also needed in order to expand and sustain the economic process such as in the agriculture, electricity usage or production, and transport. (Urban, 2009).